Product Evaluation, Strategy & Marketing at Negotiation Power - Sridharan, Niranjan (2009)
The phenomenal dotcom burst during early 2000 has now almost been completely forgotten by groundbreaking changes in the way the internet works – in both innovative business models and means of reaching customers. Even before the inception of the popular social networking sites such as Facebook and Linkedin, Kenny & Marshall (2000) wrote in their popular HBR article about the ubiquitous nature of the internet – “ New technologies are emerging that will enable businesses to reach customers whenever and wherever they are ready to buy. The focus of e-commerce will shift from content to context, knocking many corporate Web sites into irrelevance.”